Channelrhodopsin Excitation Contracts Brain Pericytes and Reduces Blood Flow in the Aging Mouse Brain in vivo - Nelson, Amy R.; Sagare, Meghana A.; Wang, Yaoming; Kisler, Kassandra; Zhao, Zhen; Zlokovic, Berislav V. (Frontiers in Aging Neuroscience, 2020)
Brain depends on blood flow for delivery of oxygen and nutrients essential for proper neuronal and synaptic functioning. French physiologist Rouget was first to describe pericytes in 1873 as regularly arranged longitudinal amoeboid cells on capillaries that have a muscular coat, implying these are contractile cells that regulate blood flow. Although, there have been >30 publications from different groups including our group demonstrating that pericytes are contractile cells that can regulate hemodynamic responses in the brain, the role of pericytes in controlling cerebral blood flow (CBF) has not been confirmed by all studies. Moreover, recent studies using different optogenetic models to express light-sensitive channelrhodopsin-2 (ChR2) cation channel in pericytes were not conclusive; one, suggesting that pericytes expressing ChR2 do not contract after light stimulus, and the other, demonstrating contraction of pericytes expressing ChR2 after light stimulus. Since two-photon optogenetics provides a powerful tool to study mechanisms of blood flow regulation at the level of brain capillaries, we re-examined contractility of brain pericytes in vivo using a new optogenetic model developed by crossing our new inducible pericyte-specific CreER mouse line with the ChR2 mice. We induced expression of ChR2 in pericytes with tamoxifen, excited ChR2 by 488 nm light, and monitored pericyte contractility, brain capillary diameter changes, and red blood cell (RBC) velocity in aged mice by in vivo two-photon microscopy. Excitation of ChR2 resulted in pericyte contraction followed by constriction of the underlying capillary leading to approximately 8% decrease (p = 0.006) in capillary diameter. ChR2 excitation in pericytes substantially reduced capillary RBCs flow by 42% (p = 0.03) during the stimulation period compared to the velocity before stimulation. Our data suggests that pericytes contract in vivo and regulate capillary blood flow in the aging mouse brain. By extension, this might have implications for neurological disorders of the aging human brain associated with neurovascular dysfunction and pericyte loss such as stroke and Alzheimer’s disease.